Płynność natychmaistowa a efektywność gospodarowania spółdzielni mleczarskich - Chmielewska, Marzena (Cash Liquidity and Efficiency of Farming of Creamery Cooperative, 2007)
In the literature there is not any one-valued and accepted standard of cash liquidity ratio. Dairy cooperatives analyzed in the paper achieve the highest efficiency of farming according to cash liquidity indices. For the analysis 37 dairy cooperatives were chosen. Then they were divided in four groups according to the level of cash liquidity ratio. It is possible to accept on the basis of carried analysis for optimal largeness this ratio for cooperative creamery at the level of 0.2. Creamery cooperatives already achieve the night efficiency of activity from this level of cash liquidity ratio.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 46-55